2016
DOI: 10.1108/tqm-12-2014-0104
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better visual inspection of products

Abstract: Purpose Visual inspection is used to assess a product’s quantitative characteristics (physical inspection) and/or to assess a product’s qualitative characteristics (sensory inspection). Due to the complexity of the product, inspection tasks are often performed by humans and are therefore prone to errors. It is particularly the case when controllers have to detect aesthetic anomalies, to evaluate them and decide if a product must be rejected or not. The paper details how to improve visual inspection. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…a single activated surface and inert walls. 7,8 Additionally, the precipitation of a salt film 40,[43][44][45][46][47][48] at high anodic potentials in corrosive solution leads to diffusion-limited dissolution -a quasi-steady state condition that permits the study of one-dimensional mass transport. Consequently, the presence of a salt film at the corroding surface was considered necessary as a critical condition for stable pitting.…”
Section: -31mentioning
confidence: 99%
See 1 more Smart Citation
“…a single activated surface and inert walls. 7,8 Additionally, the precipitation of a salt film 40,[43][44][45][46][47][48] at high anodic potentials in corrosive solution leads to diffusion-limited dissolution -a quasi-steady state condition that permits the study of one-dimensional mass transport. Consequently, the presence of a salt film at the corroding surface was considered necessary as a critical condition for stable pitting.…”
Section: -31mentioning
confidence: 99%
“…Galvele's formulation, originally intended to describe the conditions leading to pit initiation, has also been successfully extended to pit propagation. 4,7,[35][36][37] Experimental assessment of the Galvele pit model is typically performed using the artificial pit or lead-in-pencil electrode, 4,7,[39][40][41][42] which consists of a metal wire embedded in epoxy. The lead-in-pencil electrode is particularly useful because it closely represents Galvele's pit model configuration, i.e.…”
mentioning
confidence: 99%
“…18,[36][37][38] For a theoretical one-dimensional pit, Galvele 18 demonstrated that a critical product of the current density and pit depth -(i · x) -must be maintained within the pit to prevent repassivation. This parameter, later termed the pit stability product, 39 quantitatively represents the steady-state condition arising from the competition between the metal dissolution and diffusion fluxes 40,41 which results in the maintenance of a sufficiently aggressive concentration of metal cations at the actively dissolving surface for continued pitting.…”
mentioning
confidence: 99%
“…6,7 This critical pit stability product (denoted (i·x) crit ) has been employed as the anodic stability parameter to determine the maximum pit size that can be attained on a particular metal surface in a given corrosive environment. [8][9][10][11] Experimental results obtained using the artificial pit or lead-inpencil electrode [12][13][14][15][16][17] can be directly used to quantify 1-D dissolution kinetics because the construction of this electrode results in inert walls surrounding a single active surface 13,14,16 corroding under a precipitated salt film [18][19][20][21][22][23][24] upon the application of high anodic potential in corrosive solution. The presence of the salt film results in diffusionlimited dissolution conditions that permit the study of the corroding system in a quasi-steady state.…”
mentioning
confidence: 99%